THE CONCEPT OF FORESTRY AS AN OBJECT OF CONTROL AND SUPERVISION (Bulletin of criminological association of Ukraine, 2024)
It has been established that supervision and control in the field of forestry is an activity regulated by the norms of current legislation of specially authorized state authorities, as well as other state and non-state institutions, which is aimed at verifying the state of compliance with the requirements of forest law by all, without exception, subjects of forest legal relations, as well as assessing the actual state of conducting relevant activities, identifying violations, preventing them, and determining the factors that cause the commission of violations in the studied area of public life. It is argued that forestry, as an object of control and supervision, is a system of social relations that arise in the process of ensuring the protection, rational use, reproduction and management of forest resources, which is subject to verification and assessment by authorized state and non-state subjects in order to ensure legality, environmental safety and compliance with the requirements of forest and environmental legislation. It has been proven that the key features of forestry, as an object of control and supervision, are: it has significant ecological, social and economic significance; social value, because the forest is a national wealth and has strategic importance for the development of the state and society; it is clearly regulated by legislation; complexity, because the relevant control covers not only environmental aspects, but also the economic activities of individuals and legalentities in the studied sphere of public life; high probability of committing offenses in this sphere, which is due to the high probability of illegal logging, corruption, abuse; irreversibility of the consequences of committing offenses in the studied sphere of public life.
Keywords: forest; forestry; supervision; control; legality; legal regulation; legal relations